2001
DOI: 10.1046/j.0962-1083.2001.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the malaria mosquito Anopheles arabiensis across Nigeria suggests range expansion

Abstract: Ten microsatellite loci, four located within and six outside chromosome inversions, were employed to study the genetic structure of Anopheles arabiensis across the ecological zones of Nigeria (arid savannah in the north gradually turns into humid forest in the south). Regardless of location within or outside inversions, genetic variability at all loci was characterized by a reduction in both the number of alleles per locus and heterozygosity from savannah to forest. Across all loci, all but one allele in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…gambiae s.s. Giles and An. arabiensis Patton, are the most widely distributed and are amongst the most efficient vectors of human malaria known anywhere in the world (White, 1974;Coetzee et al, 2000;Onyabe and Conn, 2001). An.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae s.s. Giles and An. arabiensis Patton, are the most widely distributed and are amongst the most efficient vectors of human malaria known anywhere in the world (White, 1974;Coetzee et al, 2000;Onyabe and Conn, 2001). An.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Matthews et al (2007) recently conÞrmed the expansion of An. arabiensis populations within Nigeria, which had been suggested earlier (Onyabe and Conn 2001), and observed a stronger expansion signature in northern localities. These sites are situated in the Sudan savanna zone, near the south border of Niger and not far from our sampling sites.…”
Section: Discussionmentioning
confidence: 69%
“…arabiensis West African populations. A study conducted in Nigeria (Onyabe and Conn 2001) showed signiÞcant differentiation both within and between ecological zones, although F ST values for between zones comparisons were far greater. These results suggesting low gene ßow contrast with the data presented in this study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…comorensis Brunhes, le Goff and Geoffroy (Gillies and DeMeillon, 1968;White, 1974 and1985;Hunt et al, 1998;Harbach, 2003;Coetzee et al, 2013). Amongst these sibling species, A. gambiae and A. Arabiensis are the two major malaria vectors in Africa (Gillies and De Meillon 1968), particularly in Nigeria (Boreham et al, 1979;Onyabe and Conn, 2001;Obembe and Awopetu, 2014). There are strains of A. gambiae complex sibling species in which the parasite cannot complete its life cycle; such strains are said to be refractory (Collins et al, 1986;Chris et al, 2011;Obembe and Awopetu, 2014).…”
Section: Introductionmentioning
confidence: 99%